Hubungan pengetahuan dan sikap masyarakat dengan tindakan pencegahan penyakit demam berdarah dengue di Kelurahan Tuminting - Pantouw, Rinaldo G.; Siagian, Iyone E. T.; Lampus, Benedictus S. (UNIVERSITAS SAM RATULANGI, 2017)
Dengue Hemorrhagic Fever (DHF) is still one of the major public health problem in Indonesia. World Health Organization (WHO) estimates that about 50-100 million cases of DHF occur each year in endemic areas, with a death rate of approximately 20,000 deaths. The objective is to analyze the relationship between knowledge and attitude of the community with preventive action of dengue hemorrhagic fever in Tuminting Village. This study was conducted with cross sectional analytic method. This study will be conducted in Tuminting Village from October 2015 through December 2015. The research sample take 95 heads of families using proportional simple random sampling. The results showed that most respondents (63%) have good knowledge about the prevention of DHF, the attitude of the majority of respondents (73%) regarding the prevention of DHF has been good, most respondents (66%)Â action on the prevention of DHF has been good. From the results of the bivariate analysis there is no relation between knowledge with the DHF prevention measures, and there is no relationship between attitude and preventive measures of DHF.Keywords: dengue hemorrhagic fever, knowledge, attitude, action